The Effect Of Arrowroot Starch (Marantha Arundiceae L) Into Alginate Towards Alginate Impression Setting Time - Yustri Anita, Lelly; Agustiono, Purwanto (Insisiva Dental Journal, 2012)
The demand of alginate increase overtime, in otherhand, Indonesia could not produce its own alginate yet. Limited access to get alginate in certain region of Indonesia raise an idea to apllicate arrowroot starch into alginate to reduce alginate using. One of impression material requirment is has suitable setting time. The effect of adding arrowroot starch into alginate towards its dimensional stabillity has been published, but the effect toward its setting time has not been evaluated. Methods : This study using 60 sample that divided into 4 groups (control, 45%, 50%, and 55% of added arrowroot starch). Acrilic stick is used by entering it into alginate after 10 second, and replied until no alginate on acrilic stick. The time when no alginate on acrilic stick was record by stopwatch. Result : Statistically, KruskallWallis test is show that arrowroot starch which add into alginate have significant effect towards alginate impression setting time with p=0,000. Conclusion : Arrowroot starch which has been added into alginate has an effect towards alginate impression setting time.